Egg allergy in patients over 14 years old suffering from atopic eczema - Celakovská, Jarmila; Ettlerová, Květuše; Ettler, Karel; Vaněčková, Jaroslava (International journal of dermatology, 2011)
OBJECTIVE: The aim of this study was to evaluate the occurrence of egg allergy in patients over 14 years old suffering from atopic eczema and especially to evaluate if egg allergy can deteriorate the course of atopic eczema in this group of patients. MATERIALS AND METHODS: Altogether 179 patients suffering from atopic eczema were included in the study: 51 men and 128 women, with an average age of 26.2 years (SD 9.5 years), with median SCORAD 31.6 (SD 13.3) points. A complete allergological and dermatological examination was performed on all patients, including diagnostic work-up of food allergy to egg [skin prick tests, atopy patch tests (APTs), measurement of specific IgE level to egg yolks or whites]. Open exposure test (OET) with egg was performed in patients with positive results in some of these diagnostic methods. Food allergy to egg was determined according to positive results in the OET or according to sufficient anamnestical data about the severe allergic reaction after the ingestion of an egg. RESULTS: An allergy to egg was confirmed in 11 patients out of 179 (6%). Of these patients, only six (3.3%) had a clear improvement in the SCORAD after the elimination of egg. Other triggering factors may cause exacerbation of the atopic eczema in the patients enrolled in the study. Twenty-eight percent of patients were only sensitized to egg without clinical symptoms. ATPs were a useful tool in the diagnosis of food allergy to egg in patients without IgE reactivity. CONCLUSION: Egg allergy may play an important role in the worsening of atopic eczema acting as a triggering-exacerbating factor in a minority of patients. The diagnostic work-up may comprise the challenge tests to confirm the food allergy to egg.
Keywords: Young Adult; Male; progrese nemoci; mladý dospělý; Adolescent; Eggs; atopická dermatitida; Adult; dospělí; mužské pohlaví; Disease Progression; vaječné proteiny; potravinová alergie; Severity of Illness Index; mladiství; vejce; Food Hypersensitivity; lidé; Dermatitis, Atopic; ženské pohlaví; Humans; Age Distribution; věkové rozložení; stupeň závažnosti nemoci; Egg Proteins; Female; lidé středního věku; Middle Aged